Fabrication and characterization of a novel mullite-stainless steel composed hollow fibre membrane for oil/water separation - Suriani Abu BAkar (Tanjung Malim, 2024)
Fabrication and characterization of a novel mullite-stainless steel composed hollow fibre membrane for oil/water separation by Suriani Abu BAkar